A COMPARATIVE STUDY OF COOPERATIVE PRINCIPLE IN FACEBOOK AND TWITTER - Nadina Nurul Hasanah, - (2011)
The title of this paper is "A Comparative Study of Cooperative Principle in Facebook and Twitter". The tendency of people to communicate use social networks as a tool of communication has become an interesting object to investigate. This study conducted to identify the way the users of social networks cooperated in their conversation according to Grice's cooperative principle. The data were collected through observing 20 Facebook status and 20 Twitter tweets. The data were analyzed by using the Grice's maxim cooperative principles: quality, quantity, relevance, and manner. This research applied descriptive method in order to provide a systematic description of a situation or condition of a phenomenon as factual as possible. The analyses show that in Facebook maxim of quantity is the most frequent with 59 times of appearances or 57.84% of the total appearances. And the least frequent is maxim of manner with one appearance (0.98%). While in Twitter, the most frequent of Grice's cooperative principles is maxim of quantity too with 16 times occurrences (51.61%) and maxim of quality is the least frequent. This phenomenon happened in Facebook because there is no limitation of character for the users to write down their comments. Thus the Facebook users can write what is in their mind as much as they want. Though in Twitter, the users rarely break a maxim because there is a limitation of the characters in one tweet. The reason why Facebook users used such cooperative principle is to give a clear information to the hearer. This is in line with the clarity principle in Leech's politeness principle.